2016
DOI: 10.1007/s13277-016-4981-6
|View full text |Cite
|
Sign up to set email alerts
|

Roles of microRNA-124a and microRNA-30d in breast cancer patients with type 2 diabetes mellitus

Abstract: The aim of the study is to explore roles of microRNA (miR)-124a and miR-30d in breast cancer (BC) patients with type 2 diabetes mellitus (T2DM). A total of 144 cases of confirmed diagnosed BC with T2DM, T2DM, BC, or healthy people were enrolled. Among them, BC patients with T2DM were regarded as the experiment group (n = 36), patients with T2DM as the Dm group (n = 36), patients with BC as the Bc group (n = 36), and healthy subjects as the healthy group (n = 36). The fasting insulin resistance index, glycosyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…Moreover, there is convincing evidence that miR-30d serves as a novel prognostic biomarker in breast cancer in patients with type 2 diabetes mellitus. 14,15 Consistent these results, we found that miR-30d was increased in breast cancer cell lines and miR-30d overexpression promotes cell growth and metastasis whilst inhibiting cell apoptosis.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, there is convincing evidence that miR-30d serves as a novel prognostic biomarker in breast cancer in patients with type 2 diabetes mellitus. 14,15 Consistent these results, we found that miR-30d was increased in breast cancer cell lines and miR-30d overexpression promotes cell growth and metastasis whilst inhibiting cell apoptosis.…”
Section: Discussionsupporting
confidence: 82%
“…Evidence indicated that the expression of miR‐30d was increased in multiple types of cancers, including breast cancer with type 2 diabetes mellitus . Firstly, we found that miR‐30d expression was markedly increased in breast cancer cell lines BT474, MDA‐MB‐231, HCC197, and MDA‐MB‐468 compared with the control normal cells MCF‐10A (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-3202 could promote endothelial cell apoptosis by directly targeting Fas apoptotic inhibitory molecule 2 (FAIM2) gene in high glucose condition [Huang et al, 2017]. The miR-124a expression is reduced while miR-30d expression is increased, which showing that miR-124a and miR-30d may be associated with clinicopathological characteristics of breast cancer patients with type 2 diabetes mellitus (T2DM) [Zhang et al, 2016]. Similarly, in the current study, the level of miR-106b is obviously decreased in diabetic mice and NIT-1 cells with high glucose induction.…”
Section: Discussionmentioning
confidence: 99%
“…Documents have been accumulated to investigate the expression and role of other members of miR-30 family in human cancers [119-123]. As shown in Table 2, miR-30 family members were involved in processes of cancer development, concluding proliferation, migration, invasion, EMT, metastasis, autophagy and apoptosis through distinguished targets [124-126].…”
Section: Activities Of Mir-30a In Cancer Progressionmentioning
confidence: 99%